TENDINŢE Şl PRIORITĂŢI ÎN ACTIVITATEA BIBLIOTECILOR PUBLICE - OSOIANU, director adjunct, Biblioteca Naţionala a Republicii Moldova, Vera (BIBLIOPOLIS, 2020)
The article presents an analysis of devel-opment trends based on the experience of libraries at home and abroad and the results of sociological surveys conducted in recent years. A special place is reserved for user needs that form the basis of all positive changes in recent years, and some aspects of community involvement in library work, communication as a new concept that focuses on knowledge creation. Based on the analysis of trends and recent researches results were mapped priority activity in 2013.